UPLC-Q-TOF/MS-based screening and identification of the main flavonoids and their metabolites in rat bile, urine and feces after oral administration of Scutellaria baicalensis extract. (1st July 2015) - Du, Le-yue; Qian, Da-wei; Shang, Er-xin; Liu, Pei; Jiang, Shu; Guo, Jian-ming; Su, Shu-lan; Duan, Jin-ao; Xu, Jun; Zhao, Min
Abstract: Ethnopharmacological relevance: Traditional Chinese Medicines (TCMs) are increasingly used in combination with Western medicine. Scutellaria baicalensis Georgi (Lamiaceae) is a widely used TCM in treating various diseases. However, the in vivo metabolism of its main bioactive flavonoids, baicalin, baicalein, wogonoside and wogonin, needs further study. Materials and methods: A systematic method based on ultra-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF/MS) technique combined with Metabolynx TM software was developed to speculate the metabolites and excretion profiles of the main flavonoids in S. baicalensis extract in rats bile, urine and feces samples after oral administration of the extract. Results: Four parent components and a total of 15 metabolites were tentatively detected in vivo . All metabolites were detected including sulfate and glucuronide conjugates, hydroxylated, methylated, acetylated and deoxygenated products. Twelve metabolites were from the rat urine, five from the feces and two from the bile. Among them, several products were reported firstly. Conclusion: The research provided useful information for further study of the pharmacology and mechanism of action of S. baicalensis extract in vivo and a proposed method which could develop an integrated template approach to analyze screening and identification of biological samples after oral administration of TCMs. Graphical abstract: